Determination of Neutron Flux in Brain Cancer Boron Neutron Capture Therapy Using Monte Carlo Simulation - Arianto, Fajar; Handayani, Liska Tri; Budi, Wahyu Setia; Basuki, Prasetyo (Physics Communication, 2022)
Boron Neutron Capture Therapy (BNCT) is a relatively safer technology for killing cancer cells, one of which is the Glioblastoma multiforme. One of the main components of the BNCT equipment is the collimator which functions as an exit point for epithermal neutron particles that hit cancer cells. In addition to the experimental method, BNCT research can be carried out by modeling, including using the MCNPX software based on the Monte Carlo Method. This research aimed to determine the flux distribution of fast and epithermal neutrons and the dose rate of fast neutrons and gamma that hit the target cancer cells in the phantom head of ORNL MIRD. Modeling using the MCNPX software has three main parts: cell cards, surface cards, and data cards. A tally is used on the data card to calculate the neutron flux. Based on the calculation of the modeling results, the flux of epithermal neutron is 2.87 x 109 n/cm2.s. The dose ratio of the epithermal to the fast neutron flux is 2.29 x 10-14 Gy.cm2/n. Then, the balance of the dose rate of the epithermal to the gamma is 1.64 x 10-14 Gy.cm2/n, and the ratio of epithermal to thermal neutron flux is 0.004. In this study, the epithermal neutron flux hitting the target cancer cells in cell target was moderated at 4 cm so that at a depth of 8 cm, the energy was converted into thermal neutrons. Based on the analysis of the results, it can be concluded that the neutron flux that will interact with cancer tissue is thermal neutrons, not epithermal neutron flux.